Rainy day funds? How men and women adapt to heavy rainfall shocks and the role of cash transfers in Mali - Hidrobo, Melissa; Mueller, Valerie; Roy, Shalini; Fall, Cheikh Modou Noreyni; Lavaysse, Christophe; Belli, Anna (International Food Policy Research Institute, 2024)
Weather shocks can affect men and women differently, due in part to differences in their adaptive capacities. We merge weather data with survey data from a randomized control trial of a cash transfer program in Mali to describe how men and women cope with weather shocks and the role of cash transfer programs in supporting adaptive responses. We find that heavy rainfall reduces household’s consumption but that the cash transfer program mitigates these impacts, primarily by allowing households to draw down both men’s and women’s savings, increasing the value of livestock and farming assets held jointly by men and women, and facilitating a reallocation of men’s and women’s labor to livestock production and women’s labor to domestic work.